Energy Audit in the Facilities of the Transport Operations and Maintenance Center (COMT) - Salazar Aviles, Damaris Eunice (2023)
The diagnosis of electrical installations included field visits, measurements of electrical parameters and power quality tests. Consequently, it was crucial to describe the current state of the company's electrical system in comparison with the current standards NTE INEN 2969 and ARCONEL, related to lighting levels and energy quality, respectively. Since the installed load is broken down by zones and the group that represents the highest energy consumption per month is identified, the selection of measures to improve energy efficiency is based on an examination of the existing situation. The investigation demonstrates and concludes that the request for a modification in the rate schedule would mean a substantial saving of $2,579,904 per year.